FUNCTIONS AND LEGALITY IN EFFORTS TO IMPROVE MICRO BUSINESS IN INDRAJAYA PIDIE DISTRICT - Boini, Usman Boini; Juliaden Jayus (stiatabalong.ac.id, 2024)
The purpose of this study was to determine the function and legality of efforts to improve micro businesses in Indrajaya Pidie District. Community empowerment can be said to be good. The task functions carried out, such as providing counseling to people's economic businesses, checking the recording of funds given to people's economic businesses, supervising and reporting the results of activities on the development of people's economic businesses in Indrajaya District in improving micro businesses. The approach used in this research is a Qualitative approach, this approach is used to understand and interpret the meaning of an event, the interaction of human behavior in a particular situation. In this study using two data models, namely Primary Data, the data that will be used in this study is data derived from interviews with micro business actors in Indrajaya District and Secondary Data, Secondary data is obtained from data inventoried by micro business actors relating to the issue of functions and legality in this study. improve micro-businesses. Furthermore, to conduct this research, researchers used observation, interview and documentation techniques to be more in line with the research mote, namely descriptive qualitative. Microbusiness functions and legality are important things that must be considered for business continuity in improving microbusinesses. The results of the micro business function research play a very important role and must have a business license which is the strength of business legality in carrying out its operations. As many as 78% of microbusinesses in Indrajaya District have functioned well in improving the economy of the lower community and have had a business license from the authorized party. Efforts made in overcoming obstacles to micro businesses in Indrajaya Subdistrict maximize operational time and improve product quality and implement good marketing programs and management. In order to improve better businesses so that the regional economy can increase, especially the level of community welfare is achieved. In addition, the local government needs to increase community motivation in business development, provide guidance and guidance directed at creating a better economic structure in the region, so that the assistance of the national community empowerment program can be useful, especially in developing people's economic businesses. After the research is carried out, it can be concluded that the function and legality of micro businesses in Indrajaya District, Pidie Regency so far in increasing micro businesses is good. Thus it can be seen that the strength of micro businesses in terms of function and legality is good. Micro business development that has been carried out by business actors who have a license status is good Keywords: Function, Legality, Micro Enterprises